Holistic Empowerment through Productive Zakat: Evaluating Economic, Social, and Psychological Impacts on Female-Headed Households in Banyumas - Imam Alfi; Imam Ma’arif Hidayat Imam; Mahfudz Al Faozi Mahfudz (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Female-headed households represent a socially and economically vulnerable group due to limited access to capital, employment opportunities, and social support. Productive zakat programs implemented by Badan Amil Zakat Nasional (BAZNAS) are designed not only to assist beneficiaries in meeting basic needs but also to promote long-term economic independence. A holistic empowerment approach that integrates economic, social, and psychological dimensions is considered essential so that the program contributes not only to income improvement but also to strengthening individual capacity and social positioning. This study aims to examine the effectiveness of the productive zakat program implemented by BAZNAS Banyumas Regency in empowering female-headed households through an integrated economic, social, and psychological empowerment approach. This study employs a descriptive qualitative research design. The research population includes female-headed household beneficiaries of the productive zakat program, BAZNAS administrators, and business mentors. Data were collected through participant observation, in-depth interviews, and documentation studies. The data were analyzed thematically through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the productive zakat program generates positive impacts across multiple dimensions of empowerment. Economically, the program increases income, strengthens business independence, and expands access to capital and markets. Socially, it enhances social participation and strengthens local organizational networks. Psychologically, beneficiaries demonstrate improved self-confidence, greater decision-making capacity, active participation, and stronger mental resilience. The productive zakat program proves to be an effective instrument for empowering female-headed households. Program sustainability should be strengthened through continuous business mentoring, integration of psychosocial support, and expansion of market networks to ensure long-term empowerment outcomes.